Seedling growth of Schizolobium parahyba on different substrates and irrigation levels - Sabonaro, Débora Zumkeller [UNESP]; Galbiatti, João Antonio [UNESP] (My University, 2011)
The present study aimed to assess the behavior of seedlings of Schizolobium parahyba (Vell.) Blake growing on different substrates and irrigation levels, and to study the use of urban waste compost in substrates. The experiment was carried out in the College of Agricultural Sciences, Universidade Estadual Paulista (UNESP), Department of Agricultural Engineering, Jaboticabal Campus, state of São Paulo, Brazil. The experimental design used was completely randomized, consisting of 30 treatments in a factorial design with 15 substrates and two irrigation levels in four replicates. The substrates were composed of different materials: urban waste, Plantmax®, dry cattle manure, vermiculite and soil. For the study of seedling growth, the following characteristics were evaluated: height (H), root-collar diameter (D), number of leaves, shoot dry weight, root dry weight, total dry weight, H/D ratio, Dickson's quality index, and the ratio between height and shoot dry weight (H/SDW). Assessments of the first three characteristics were carried out 20, 35, 50 and 65 days after sowing. Results showed that urban waste compost increased the growth of Schizolobium parahyba. There were significant differences for the irrigation levels tested; with better results for 150% ET compared to 100% ET irrigation level.
Keywords: Native species; Soil fertility; Urban waste compost; Bos; Schizolobium parahyba